Differences in prey availability across space and time lead to interaction rewiring and reshape a predator–prey metaweb. Issue 8 (19th May 2022) - Ceron, Karoline; Provete, Diogo B.; Pires, Mathias M.; Araujo, Andréa C.; Blüthgen, Nico; Santana, Diego J.
Abstract: Space and time promote variation in network structure by affecting the likelihood of potential interactions. However, little is known about the relative roles of ecological and biogeographical processes in determining how species interactions vary across space and time. Here we study the spatiotemporal variation in predator–prey interaction networks formed by anurans and arthropods and test for the effects of prey availability in determining interaction patterns, information that is often absent and limits the understanding of the determinants of network structure. We found that network dissimilarity between ecoregions and seasons was high and primarily driven by interaction rewiring.We also found that species turnover was positively related to geographical distance. Using a null model approach to disentangle the effect of prey availability on the spatial and temporal variation, we show that differences in prey availability were important in determining the variation in network structure between seasons and among areas. Our study reveals that fluctuations in prey abundance, alongside the limited dispersal abilities of anurans and their prey, may be responsible for the spatial patterns that emerged in our predator–prey metaweb. These findings contribute to our understanding of the assembly rules that maintain biotic processes in metacommunities and highlight the importance of prey availability to the structure of these systems.